Transmigration village development: the state and community organizations in rural Indonesia - Nurlinah; Haryanto (Frontiers in Political Science, 2024)
Indonesia’s transmigration areas are recognized for failing to fulfill advancement necessities, particularly spearheading progress in remote rural regions. Despite the dynamic characteristics, Village Community Organizations (VCOs) have made transmigration village development more progressive and promising. Therefore, this study aimed to explore the engagement of VCOs, such as economic, women, and youth organizations, in developing transmigration areas. This study uses qualitative methods with data collection techniques in the form of observation and in-depth interviews in nine villages in Indonesia. A community-driven development approach was used to analyze the development of transmigration villages. The study further identified three main factors: social capital, education, and support from the village government for VCO initiatives. These factors significantly influenced the actions to foster development within each transmigration village. The results provided significant insights into the crucial role of VCOs in empowering transmigration areas. This study recommends that policymakers apply this model to encourage greater community involvement, where strengthening resources in VCOs will increase community participation in sustaining rural development. The study further complemented previous publications by examining the role of VCOs, which was neglected in developing countries such as Indonesia.